Boundary value problems of differential inclusions with Riemann-Liouville fractional derivative - Benchohra, M.; Djebali, S.; Hamani, S. (Нелінійні коливання, 2011)
In this paper, we establish sufficient conditions for the existence of solutions for a class of boundary value problem for fractional differential inclusions involving the Riemann-Liouville fractional derivative. The cases of both convex and nonconvex valued right-hand side are considered. The topological structure of the set of solutions is also examined.